NORMATIVE OBSERVATIONS OF DEEP SOIL MIXING TECHNOLOGY OF SOIL-CEMENT PILES MANUFACTURING - Zotcenko, M.; Petrash, S.; Petrash, P.; Petrash, O. (Academic journal Industrial Machine Building Civil Engineering, 2017)
This article deals with the complex process of pile foundation erection for civil building. Deep soil mixing (DSM) technology is used. In order to find material, necessary for the proper costing designing normative observations of DSM technology of RSCP manufacturing were carried out using method of photo recording. Using that, labor spends of machines and workers for a single unit of production as well as norm of time were calculated. Comparison algorithm that can be used for different techniques, conditions ways of construction organization and other factors is presented. This methodic allows determining of the influence of different factors of construction production and environment to the process of RSCP manufacturing. Compiled results of this investigation and follows ones will allow adequate costing system for DSM technology to be created given that a necessary amount of a practical data will be accumulated. Keywords: pile, soil-cement, reinforcement, technology, costing, labor costs, timing, norm.